2011
DOI: 10.1590/s1807-59322011001100010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of symptoms of urinary incontinence in women with polycystic ovary syndrome

Abstract: OBJECTIVES:The pelvic floor muscles are sensitive to androgens, and due to hyperandrogenism, women with polycystic ovary syndrome can have increased mass in these muscles compared to controls. The aim of this study is to compare reports of urine leakage and quality of life between women with and without polycystic ovary syndrome.METHODS:One hundred thirteen 18- to 40-year-old nulliparous women with polycystic ovary syndrome or without the disease (controls) were recruited at the University Hospital of School M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…This supports, the notion that pelvic floor muscle strengthening exercise may improve SUI symptoms by increasing androgen levels locally. Intriguing data from studies conducted in women with polycystic ovarian syndrome (PCOS), a hyper‐androgenic disorder (>70 ng/dL of testosterone compared to 15–50 ng/dL in normal pre‐menopausal women) have demonstrated that PCOS can eliminate the increased risk for UI observed in obese women and that obese women with PCOS have a similar prevalence of UI as those considered to have a normal body mass index [Montezuma et al, ]. In a separate study, although pelvic floor muscle strength was not different, none of the women with PCOS suffered from UI compared to matched controls in which 18.6% had UI [Antonio et al, ].…”
mentioning
confidence: 97%
“…This supports, the notion that pelvic floor muscle strengthening exercise may improve SUI symptoms by increasing androgen levels locally. Intriguing data from studies conducted in women with polycystic ovarian syndrome (PCOS), a hyper‐androgenic disorder (>70 ng/dL of testosterone compared to 15–50 ng/dL in normal pre‐menopausal women) have demonstrated that PCOS can eliminate the increased risk for UI observed in obese women and that obese women with PCOS have a similar prevalence of UI as those considered to have a normal body mass index [Montezuma et al, ]. In a separate study, although pelvic floor muscle strength was not different, none of the women with PCOS suffered from UI compared to matched controls in which 18.6% had UI [Antonio et al, ].…”
mentioning
confidence: 97%
“…It was not possible to perform a metanalysis due to the heterogeneity of the instruments used to assess outcomes among the studies. All of them had a cross-sectional design [8][9][10][11][12][13][14][15][16] , and most of them were performed in Brasil (n=6), followed by China, Iran, and Turkey (n=1), comprising 1,132 women. Four of them 9,11,12,15 did not inform the study period, and five presented a variation of 4 to 24 months of data collection (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies, despite not presenting significant differences among the groups, show that the presence of circulating androgens may generate more muscle thickness 9 and strength 14 . On the other hand, PCOS women may present a worse quality of life, more prolapse, and urinary symptoms 10,11,15 . Central obesity caused by PCOS may increase bladder pressure and urethral mobility, contributing to urinary incontinence 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Their findings indicated that the control group with BMI >25 kg/m 2 had a higher level of stress incontinence. 48 Furthermore, Taghavi et al, in a study on 103 PCOS women and 99 controls, found that the BMI had no significant affect on the pelvic organ prolapse distress. 23 Melo et al found that pelvic floor muscle thickness of PCOS patients was not different from the control group; however, the mean BMI of control group and PCOS was 22.5 kg/m 2 and 27.8 kg/m 2,57 respectively.…”
Section: Obesitymentioning
confidence: 99%
“…Although it has been suggested that high androgen levels in women with PCOS and the presence of androgen receptors in the urinary tract may have a protective role on pelvic floor muscle function, there is still insufficient evidence to support the protective role of PCOS in pelvic floor muscle dysfunction. 48 In a crosssectional study of 42 PCOS patients and 13 premenopausal women, Micussi and colleagues reported that the serum levels of estradiol and testosterone correlated with pelvic floor muscle tone and that maximum voluntary contraction (MVC) and PCOS patients had higher electromyographic value; in other words, the hyperandrogenism in these patients had a protective effect on pelvic floor muscles. 49 Future studies are needed to investigate the potential effect of hormonal imbalance and pelvic organ function in women with PCOS.…”
Section: Hormonal Changesmentioning
confidence: 99%